A novel methodology for measuring batch settling velocities of particles using Electrical Resistance Tomography. (15th March 2022) - Chinedu Anyaoku, Chukwunonso; Bhattacharya, Sati N; Parthasarathy, Rajarathinam
Highlights: Glass microparticles were made to settle in aqueous glycerol of 80, 85 and 90 wt% glycerol. Settling velocities were measured using Electrical Resistance Tomography. The vessel was inclined to yield tomograms measuring concentration gradients across a vertical height. A model was developed to convert the concentration gradient data to settling velocities. Measured settling velocities had accuracies of between 84 and 98% when compared with values predicted by the Richardson and Zaki model. Abstract: This study demonstrates how to measure batch settling velocities of particles in columns at an unconventionally high vertical spatial resolution of 1 mm using Electrical Resistance Tomography (ERT). A novel methodology, which utilized a titled vessel fitted with an ERT sensor array and novel analytical equations, was tested on dilute Newtonian suspensions of fairly monodisperse spherical glass beads (4.8% v/v) with a d50 diameter of 123 µm in aqueous glycerol solutions at 80, 85 and 90 wt% concentrations. The model yielded settling velocities of 0.13, 0.076 and 0.043 mm/s for the three suspensions respectively, each approximating their predicted values with errors of 16.3, 14.4 and 2.29%, respectively. Data fluctuations were discerned in the dataset but their effect on the dataset quality was minimized by increasing the time step sizes by factors of 3, 4 and 9 for the 80, 85 and 90 wt% glycerol solutions, respectively.